2003
DOI: 10.1191/0265532203lt245oa
|View full text |Cite
|
Sign up to set email alerts
|

A many-facet Rasch analysis of the second language group oral discussion task

Abstract: FACETS many-facet Rasch analysis software (Linacre, 1998a) was utilized to look at two consecutive administrations of a large-scale (more than 1000 examinees) second language oral assessment in the form of a peer group discussion task with Japanese English-major university students. Facets modeled in the analysis were examinee, prompt, rater, and ve rating category 'items.' Unidimensionality was shown to be strong in both datasets, and approaches to interpreting t values for the facets modeled in the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(140 citation statements)
references
References 31 publications
8
131
1
Order By: Relevance
“…For example, in the group oral placement test described in Bonk and Ockey (2003), test takers' performances are rated on pronunciation, fluency, grammar, vocabulary/content, and communicative skills/strategies, the latter being essentially another name for interactional competence. In the group discussion task of the CET-SET, the evaluative criteria include: 1) accuracy in pronunciation, stress/intonation, and use of grammar and vocabulary, 2) range of vocabulary and grammatical structures, 3) size (percentage) of contribution to group discussion, 4) discourse management, 5) flexibility in dealing with different situations and topics, and 6) appropriateness in the use of linguistic resources (Zheng and Cheng, 2008).…”
Section: Iii2 Paired and Group Oral Discussionmentioning
confidence: 99%
“…For example, in the group oral placement test described in Bonk and Ockey (2003), test takers' performances are rated on pronunciation, fluency, grammar, vocabulary/content, and communicative skills/strategies, the latter being essentially another name for interactional competence. In the group discussion task of the CET-SET, the evaluative criteria include: 1) accuracy in pronunciation, stress/intonation, and use of grammar and vocabulary, 2) range of vocabulary and grammatical structures, 3) size (percentage) of contribution to group discussion, 4) discourse management, 5) flexibility in dealing with different situations and topics, and 6) appropriateness in the use of linguistic resources (Zheng and Cheng, 2008).…”
Section: Iii2 Paired and Group Oral Discussionmentioning
confidence: 99%
“…In all, the MFRM results suggested that rater leniency or severity was not stable over time. The findings of the current study were in line with Bonk and Ockey's (2003) findings that rater severity may change over time for individuals.…”
Section: Examining Severity Effects Of Ept Raters' Rating Behavior (Rq1)supporting
confidence: 90%
“…Several language testing studies (e.g., Bonk & Ockey, 2003;North & Jones, 2009;O'Sullivan, 2008) have employed MFRM approaches in illuminating rater severity effects in assessment processes. The underlying conceptualization of MFRM is that raters are independent readers who subjectively apply their understanding in their ratings and are not considered as 'human clones' to automatically use scoring rubric (Bond & Fox, 2007, p. 114).…”
Section: Multifaceted Rasch Measurement Analysis Of Rater Severity (Rq1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Others appear to be more skillful in handling dialogue type interview tests. Still others perform best in discussion activities (Brown 2003;Bonk & Ockey, 2003).…”
Section: Introductionmentioning
confidence: 99%